2018
DOI: 10.1155/2018/6709525
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Quantification of Magnetic Susceptibility in Gel Phantoms: Assessment of Measurement and Calculation Accuracy

Abstract: The local magnetic field inside and around an object in a magnetic resonance imaging unit depends on the magnetic susceptibility of the object being magnetized, in combination with its geometry/orientation. Magnetic susceptibility can thus be exploited as a source of tissue contrast, and susceptibility imaging may also become a useful tool in contrast agent quantification and for assessment of venous oxygen saturation levels. In this study, the accuracy of an established procedure for quantitative susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 45 publications
(49 reference statements)
1
21
0
Order By: Relevance
“…Without a gold‐standard technique, it was not possible to obtain a meaningful in vivo reference susceptibility map through measurements. The committee had also discussed the design of real‐world test objects (phantoms) that are consistent with the QSM phase model 33,34 . Based on the committee members’ experience with phantom design and a literature research of previously used phantoms, it was concluded that the inclusion of sufficiently complex morphology and fine‐scale susceptibility features would be prohibitively challenging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Without a gold‐standard technique, it was not possible to obtain a meaningful in vivo reference susceptibility map through measurements. The committee had also discussed the design of real‐world test objects (phantoms) that are consistent with the QSM phase model 33,34 . Based on the committee members’ experience with phantom design and a literature research of previously used phantoms, it was concluded that the inclusion of sufficiently complex morphology and fine‐scale susceptibility features would be prohibitively challenging.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, most QSM algorithms were evaluated based on their visual appearance, 5,24,25 based on the RMS error (RMSE) of reconstructions of simple digital piece-wise constant phantoms consisting of geometrical shapes [25][26][27][28][29][30] or simplistic head phantoms. 22,31 Evaluation of the susceptibility quantification accuracy and precision typically relied on phantoms made of agar or aqueous solutions with varying concentrations of contrast agents such as gadolinium 20,26,[32][33][34][35] or iron oxide particles. 5,28,[36][37][38] Such measurements have been of great importance in establishing that QSM linearly maps the magnetic susceptibility property and that measurements across different platforms can be compared.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, most QSM algorithms were evaluated based on their visual appearance (5,24,25), based on the root-mean-squared-error (RMSE) of reconstructions of simple digital piece-wise constant phantoms consisting of geometrical shapes (25)(26)(27)(28)(29)(30), or simplistic head phantoms (22,31). Evaluation of the susceptibility quantification accuracy and precision typically relied on phantoms made of agar or aqueous solutions with varying concentrations of contrast agents such as Gadolinium (20,26,(32)(33)(34)(35) or iron oxide particles (5,28,(36)(37)(38). Such measurements have been of great importance to establish that QSM linearly maps the magnetic susceptibility property and that measurements across different platforms can be compared.…”
Section: Limitations Of Previous Evaluation Strategiesmentioning
confidence: 99%
“…Without a gold standard technique, it was not possible to obtain a meaningful in vivo reference susceptibility map through measurements. The committee had also discussed the design of real-world test objects (phantoms) that are consistent with the QSM phase model (33,34). Based on the committee members' experience with phantom design and a literature research of previously used phantoms, it was concluded that the inclusion of sufficiently complex morphology and fine-scale susceptibility features would be prohibitively challenging.…”
Section: Design Considerations For Rc2mentioning
confidence: 99%
“…However, obtaining pixel-wise information about CA concentration in structures of arbitrary shape and orientation relative to the main magnetic field is not straightforward, and QSM is an evolving approach where different algorithms have been proposed to solve the ill-posed problem of using MRI phase information to obtain information about magnetic susceptibility distributions [16]. While promising QSM reconstruction algorithms are continuously developed, there is still need for further evaluation of the performance in challenging geometries [19]. Also, to be able to compare susceptibility values from different measurements or different time points (and thus to quantify CA concentration), a reliable reference region is needed [12].…”
Section: Introductionmentioning
confidence: 99%